Fiendish - Yovanoff, Brenna (New York : Penguin Group, 2014)
Clementine DeVore, seventeen, is determined to learn what happened ten years ago that led to her magical imprisonment and problems in her town, but a dangerous attraction to Fisher, the boy who freed her, town politics, and the terrifying Hollow get in the way.
English language and literature.
Keywords: Magic -- Fiction; Supernatural -- Fiction; Love -- Fiction; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Love & Romance